2011
DOI: 10.2355/isijinternational.51.1050
|View full text |Cite
|
Sign up to set email alerts
|

Inter-particle Percolation Segregation during Burden Descent in the Blast Furnace

Abstract: Inter-particle percolation at the interfaces between burden layers directly influences the permeability of the burden in the shaft of the blast furnace. This paper studies inter-particle percolation of small particles (pellets) into large particles (coke) during the burden descent through small-scale experiments and simulations. A special device was designed for making it possible to consider the effect of the increase in cross-sectional area along with the burden descent. The simulations, which are based on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 49 publications
(34 citation statements)
references
References 17 publications
3
31
0
Order By: Relevance
“…1), which shows that the simulation has been able to reproduce the main features. 17) Thus, the DEM simulations can be considered to be in general agreement with the experimental results. Thus, DEM modeling can be used to investigate the inter-particle percolation in burden descent, although the non-spherical coke particles are represented by spherical ones in the simulations.…”
Section: Basic Setupsupporting
confidence: 54%
See 2 more Smart Citations
“…1), which shows that the simulation has been able to reproduce the main features. 17) Thus, the DEM simulations can be considered to be in general agreement with the experimental results. Thus, DEM modeling can be used to investigate the inter-particle percolation in burden descent, although the non-spherical coke particles are represented by spherical ones in the simulations.…”
Section: Basic Setupsupporting
confidence: 54%
“…The experimental results 17) for a single coke or pellet layer revealed that with the expansion of the device, the left side of the burden surface declined and finally the surface of practically the whole bed showed an angle. For the coke, the declination of the surface profile was more pronounced while it was more regular for pellets.…”
Section: Basic Setupmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the particle i bears two kinds of torque which are tangential torque T ij and rolling friction torque M ij . [39][40][41] All the forces and torques used in the model are listed in Table 1.…”
Section: Model Formulationmentioning
confidence: 99%
“…Table 2 lists the parameters used in the simulation. 33,41,42) The mass ratios and densities of different burdens are obtained from the plant operation in Baosteel. Table 1.…”
Section: Simulation Conditionsmentioning
confidence: 99%